DIAGNOSA DEMAM TIFOID DISERTAI KONDISI KADAR LEUKOSIT PASIEN DI RUMAH SAKIT ISLAM SAKINAH MOJOKERTO - FARIHATUN NAFIAH; ROMYUN ALVY KHOIRIYAH; MISBAKHUL MUNIR (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
The first step of tifoid fever diagnosis is through the test of leukocyte levels using hemadializer. Leukocytes are a major component of body immunity, especially in the fight against infection. Early symptoms of typhoid fever resemble fever in general, so it needs to be continued with more specific test one tubex test as applied to clinical pathology laboratory Islamic Hospital Sakinah Mojokerto. The results obtained are leukocyte levels in patients divided into three categories, below normal limits, normal, and above normal levels. So the case of typhoid fever becomes very interesting to continue to be studied and presented mechanism of the infection in detail.